Pembelajaran Bernyanyi Secara Unisono Di Kelas VII-1 SMP Negeri 1 Painan Kabupaten Pesisir Selatan - Annisa Hayatul Husna; Esy Maestro (FBS Universitas Negeri Padang, 2020)
This study aimsto explain the implementation of Unisono singing learning at class VII-1 in SMP Negeri 1 Painan, Pesisir Selatan District. Type of this research wasa qualitative research with using a descriptive approach, so it was called qualitative-descriptive analysis research. By using this research method, the research process and results provided the complete and the real picture of the object under study from several points of view with a description. Techniques of data collection were collected by taking observation, interviews and documentation. Techniques of data analysis were done by collecting, identifying, classifying, describing, and finally drawing final conclusions of the research. After taking notes during the data collection including doing the interviews and document studies, the results obtain that the implementation of cultural art (music), especially on the topic of unisono singing at class VII-1 SMP Negeri 1 Painan found that the teacher still uses the usual learning methods or conventional, namely the lecture method, question and answer, and discussion. In fact, in the learning to unisono singing which requires demonstrations in the form of demonstration activities and exercises, it is rarely shown or done by the teacher in front of the students. Even if there is a pilot, the teacher only exemplifies the song to the students without demonstrating it completely, but instead sing a piece. As a result, unisono singing learning becomes subject matter of knowledge, without knowing clearly how the correct vocal technique to sing it.